An iphone application for personal noise dosimeter - Lim, Evan Boon Keat (2014)
With the ever-increasing rate of smartphone penetration around the world, especially in Singapore, smartphones are now an essential part of our lives. One of the greatly used features is the built-in music player of the smartphone. With music being as accessible as never before, there is no surprise that people are spending more time being plugged in to their earphones or headphones to listen to music. With people, especially teenagers, now being exposed to music over a prolonged period of time at relatively louder volume levels, this inevitably increases their risk of suffering from permanent noise-induced hearing loss should they not adhere to the recommended safe noise dosage level. Therefore, it is crucial to make listeners aware of the amount of noise dosage they are being exposed and whether it is within the safety limits. One way to mitigate such risk would be the use of a noise dosimeter to measure the noise dosage level.